Seven years of quasi-continuous LIDAR data. Issue 1 (1st December 2022) - Gaug, Markus; Hahn, Alexander; Acciari, Victor; Besenrieder, Jürgen; Prester, Dijana Dominis; Dorner, Daniela; Fink, David; Font, Lluís; Fruck, Christian; Mićanović, Saša; Mirzoyan, Razmik; Pavletić, Lovro; et al.
Abstract: We have analyzed seven years of quasi-continuous LIDAR data taken during those nights when the MAGIC telescopes were operating. Characterization of the nocturnal ground layer is possible through an absolute calibration of the LIDAR during clear nights and yields zenith and azimuth-angle dependent aerosol extinction scale heights for clear nights. We derive aerosol transmission statistics for light emitted from various altitudes throughout the year and separated by seasons. We find further seasonal dependencies of cloud base and top altitudes. The Cumbre Vieja volcano dust plume observation is shown to highlight the possibilities and limitations of our method.